Impact of Mechanical down Tilt and Height on the Pilot Coverage of UMTS Networks - N. Faruk; M. I. Gumel; A. Abdulkarim (Nigerian Journal of Technological Development, 2012)
The task of planning a network can be very challenging as it involves many careful studies with a lot of considerations and, at times, trial and error. In this paper, the impacts of antenna mechanical down tilt and antenna height on UMTS network performance are studied. First, we used ASSET3G simulation software to design 3G pilot coverage. Optimization techniques were deployed to study the performance of the network. Simulation results show about 2.6% increase in the coverage area when the antenna height was increased from 15 m to 25 m at the same tilt angle of 0 ° The coverage drops by 24% when transiting from 0° to 6° tilt angle was made for 15 m height antenna. The results also indicated that, pilot pollution could be reduced by choosing optimum down tilt angle.